How Immigration Identity and Intermarriage Influence Earning Ability - Zhang, Liu (Université d'Ottawa | University of Ottawa, 2015)
Using data collected by the General Social Survey of 2011, this paper tries in estimate the labour market performance of immigrants involved in different marital status situations, such as being single, being married to a native-born Canadian, and being married to another immigrant. Males and females are analyzed separately. The regression results suggest that immigrants earn less than natives and that marriage improves people’s earning ability. For immigrants, intermarriage and endogamous marriage are not much different in terms of earning ability. Immigrant males are not significantly influenced by family structure. However, immigrant females in an endogamous marriage have a higher assimilation rate than those who intermarried. Their low initial wage is offset by a higher assimilation rate.